The dumpster diver - Wong, Janet S. (Candlewick Press, 2007)
Once a month--every week in the summer--Steve the electrician dons special gear and, with the help of youngsters who live in his building, dives into a dumpster seeking useful objects that they can transform into imaginative new ones.